The First European Parabolic Flight Campaign with the Airbus A310 ZERO-G - Pletser, Vladimir; Rouquette, Sebastien; Friedrich, Ulrike; Clervoy, Jean-Francois; Gharib, Thierry; Gai, Frederic; Mora, Christophe (Microgravity science and technology, 2016)
Aircraft parabolic flights repetitively provide up to 23 seconds of reduced gravity during ballistic flight manoeuvres. Parabolic flights are used to conduct short microgravity investigations in Physical and Life Sciences and in Technology, to test instrumentation prior to space flights and to train astronauts before a space mission. The use of parabolic flights is complementary to other microgravity carriers (drop towers, sounding rockets), and preparatory to manned space missions on board the International Space Station and other manned spacecraft, such as Shenzhou and the future Chinese Space Station. After 17 years of using the Airbus A300 ZERO-G, the French company Novespace, a subsidiary of the ’ Centre National d’Etudes Spatiales ’ (CNES, French Space Agency), based in Bordeaux, France, purchased a new aircraft, an Airbus A310, to perform parabolic flights for microgravity research in Europe. Since April 2015, the European Space Agency (ESA), CNES and the ‘ Deutsches Zentrum für Luft- und Raumfahrt e.V .’ (DLR, the German Aerospace Center) use this new aircraft, the Airbus A310 ZERO-G, for research experiments in microgravity. The first campaign was a Cooperative campaign shared by the three agencies, followed by respectively a CNES, an ESA and a DLR campaign. This paper presents the new Airbus A310 ZERO-G and its main characteristics and interfaces for scientific experiments. The experiments conducted during the first European campaign are presented.